Meteorite mineralogy - Rubin, Alan 1953-; Ma, Chi ca. 20./21. Jh (Cambridge planetary science, 2021)
Meteorites are fascinating cosmic visitors. Using accessible language, this book documents the history of mineralogy and meteorite research, summarizes the mineralogical characteristics of the myriad varieties of meteorites, and explains the mineralogical characteristics of Solar System bodies visited by spacecraft. Some of these bodies contain minerals that do not occur naturally on Earth or in meteorites. The book explains how to recognize different phases under the microscope and in back-scattered electron images. It summarizes the major ways in which meteoritic minerals form - from condensation in the expanding atmospheres of dying stars to crystallization in deep-seated magmas, from flash-melting in the solar nebula to weathering in the terrestrial environment. Containing spectacular back-scattered electron images, colour photographs of meteorite minerals, and with an accompanying online list of meteorite minerals, this book provides a useful resource for meteorite researchers, terrestrial mineralogists, cosmochemists and planetary scientists, as well as graduate students in these fields